Dialektika Fenomenologis dan Rasionalitas Bertahan Hidup: Memaknai Kemiskinan pada Keluarga Miskin di Semampir, Surabaya - Agustin, Dewien Nabielah; Putri, Rizky Trisna; Pertiwi, Juliana Bulan (Jurnal Salingka Nagari, 2025)
This study aims to analyze the meaning of poverty from the perspective of poor families using a phenomenological approach. The government has defined poverty in various ways, using indicators from the Central Statistics Agency (BPS) and other institutions. Seven key informants participated in this study, all of whom had at least ten years of experience as poor families in Semampir, Surabaya. This study found that poverty forces the poor in Semampir to survive because they have no other options. The analysis shows that their vulnerability and powerlessness enable poor families to engage in a phenomenological dialectic, enabling them to survive with existing resources and jobs to meet daily needs despite facing many limitations. Kinship and employment bridge the gap. Savings or setting aside income serve as a benchmark for rationalizing what they must do to meet family needs. And the results of the data analysis indicate that limitations in how they can and how to survive are a strong reason for the inability of poor families to manage their finances.